Influence of user experience, product innovation, and customer relationship management on word of mouth with the customer satisfaction as a mediating role in by.U digital provider - Nazhifa, Nisya; Malini, Helma; Afifah, Nur; Ramadania, Ramadania; Karsim, Karsim (Institute of Computer Science (IOCS), 2024)
In an era of rapidly evolving technology, telecommunications companies must compete quickly to create product innovations that suit the ever-changing preferences of Generation Z. Telkomsel, introduced by.U., which a digital provider that prioritizes exceptional User Experience. A good User Experience has the potential to generate long-term benefits by increasing Product Innovation and establishing efficient Customer Relationship Management to develop Customer Satisfaction. Customer Satisfaction generates positive Word of Mouth recommendations. This study explored the influence of User Experience, Product Innovation, and Customer Relationship Management on Word of Mouth through Customer Satisfaction among 227 respondents from Indonesia. Data was collected through online questionnaires and analyzed using Structural Equation Model (SEM) AMOS 24. Results indicate that User Experience, Product Innovation, and Customer Relationship Management have significant impacts on Customer Satisfaction and Word of Mouth. Additionally, Customer Satisfaction mediates the relationship between User Experience and Product Innovation on Word of Mouth. An intriguing discovery was found that Customer Satisfaction does not significantly mediate the link between Customer Relationship Management and Word of Mouth. This study aims to offer valuable insights and practical recommendations for companies and marketing practitioners, aiding in the development of adaptive strategies to stay competitive in the digital era.